A qualitative study of the impact of coronavirus disease (COVID‐19) on psychological and financial wellbeing and engagement in care among men who have sex with men living with HIV in Thailand. Issue 3 (11th October 2021) - Nitpolprasert, Chattiya; Anand, Tarandeep; Phanuphak, Nittaya; Reiss, Peter; Ananworanich, Jintanat; Peay, Holly Landrum
Abstract: Objectives: The coronavirus disease (COVID‐19) pandemic is an unprecedented event with massive global health and socio‐economic impacts on vulnerable populations, especially people living with HIV. The epidemic has severely affected Thailand's economy and potentially impacted the financial and psychological wellbeing of Thai HIV‐positive men who have sex with men (MSM). Methods: Between 15 June and 10 December 2020, we conducted qualitative interviews with 26 MSM living with HIV in Thailand who participate in an Adam's Love We Care Study. We intentionally recruited individuals who may have experienced a greater impact of COVID‐19. Interviews explored worry, stigma and stress surrounding COVID‐19, and multiple domains of potential COVID‐19 impact: financial/employment, HIV service delivery and antiretroviral (ART) adherence during the first 10 months of the COVID‐19 pandemic. Results: Participants perceived themselves as immunocompromised and susceptible, and feared contracting COVID‐19. Participants worried that contracting COVID‐19 would lead to HIV status disclosure and stigmatization. Participants had considerable worry about job loss as a result of the economic downturn, and some shared challenges associated with relocation and re‐engaging with HIV care. Financial stress and lack of basic necessities caused by job losses were commonly reported. Participants reported optimal ART adherence as a consequence of local HIV service delivery responses, convenient ART refills and Adam's Love online support interventions. Conclusions: Our study highlights that the COVID‐19 pandemic produced high levels of anxiety and concerns about additional stigma among MSM living with HIV. It had a significant negative effect on the daily lives of our participants. These findings indicate a need for the provision of confidential COVID‐19 diagnosis and care, relief programmes, vaccination roll‐out equity, and addressing employment needs of vulnerable populations.